Pharmacognostical and Physico Chemical Evaluation of Jeevantyadi Taila In the Management Primary Open Angle Glaucoma - S, Adoor Veeranagowda (International Journal of Pharmaceutical & Biological Archive, 2013)
Pharmacognostical and Physico Chemical Evaluation of Jeevantyadi Taila In the Management Primary Open Angle Glaucoma